MEMBANGUN WEBSITE PROGRAM STUDI PSIKOLOGI UNIVERSITAS SAHID SURAKARTA - Sutopo, Agus; Retnoningsih, dwi; Charolina, Astri (Gaung Informatika, 2015)
PsychologyÂ MajorÂ ofÂ SahidÂ UniversityÂ SurakartaÂ isÂ underÂ theÂ FacultyÂ ofÂ HealthÂ Sciences.Â Â The information about the major is still manual and not effective. According to the improvement of information technology based on internet, website is the right solution to convey information fast and eficiently. The purpose of this researchÂ is to developÂ Psychology majorÂ of Sahid University Surakartaâs website in order to simplify the information management and delivery to the students and the society. The methodsÂ Â which areÂ usedÂ toÂ collectÂ theÂ dataÂ areÂ observation,Â interview,Â literature,Â andÂ questionnaireÂ methodÂ toÂ webQual test. The data analysis used is structured based onÂ (DFD) Data Flow Diagram, Flowchart. The making of thisÂ websiteÂ usesÂ HTML,Â PHPÂ andÂ MySQLÂ databaseÂ programming.Â ToÂ measureÂ theÂ qualityÂ ofÂ the PsychologyÂ majorÂ ofÂ SahidÂ UniversityÂ SurakartaâsÂ website,Â adjustedÂ toÂ theÂ visitorsâÂ orÂ theÂ lastÂ userâsperception, so the website test method used is webQual testing and Likert scale. From 30 questions which wereÂ askedÂ toÂ 30Â respondentsÂ andÂ theÂ dataÂ areÂ processedÂ usingÂ SPSSÂ 20,Â theÂ testingÂ resultÂ ofÂ the Psychology Major of Sahid UniversityÂ Surakartaâs website is 7.14%. ItÂ means that the Psychology Majorof Sahid University Surakartaâs website is good.